Strengthening Future Leadership through Islamic Education Management: Exploring Innovative Character-Based Leadership Models - Sahdia, Limatul; Erdi Pratama, Nanda; Fitri, Nidya; Majeedah Hamdan, Nurul (International Journal of Islamic Teaching and Learning, 2025)
Islamic education management is the process of managing educational institutions based on Islamic values, including planning, organizing, implementing, and evaluating. This research aims to examine the implementation of Islamic education management according to the perspectives of experts in order to formulate strategic principles that are relevant to contemporary challenges. This research uses a qualitative method with a content analysis approach by reviewing reliable sources such as accredited books and scientific journal articles obtained through Google Scholar with the help of Harzing's Publish or Perish application. Data analysis was conducted using the Miles and Huberman model, through the stages of data reduction, data presentation, and systematic and thematic conclusion drawing. The results of the study show that ideal Islamic education management is characterized by planning based on Islamic values, visionary leadership, synergistic collaboration, utilization of information technology, and continuous evaluation. The findings are expected to be a strategic reference for policy makers in designing an effective, quality Islamic education management system that is in line with sharia principles.